Financial markets and institutions : a European perspective - Haan, Jakob de; Oosterloo, Sander; Schoenmaker, Dirk (Cambridge University Press, 2012)
"Since the first edition of this book, the world?s financial system went through its greatest crisis for a century. What made this crisis unique is that severe financial problems emerged simultaneously in many different countries and that its economic impact was felt throughout the world as a result of the increased interconnectedness of the global economy. Written for undergraduate and graduate students of finance, economics and business, the second edition of this successful textbook provides a fresh analysis of the world financial system in light of the recent financial crisis. Combining theory, empirical data and policy, it examines and explains financial markets, financial infrastructures, financial institutions and challenges in the domain of financial supervision and competition policy. This new edition features three completely new chapters, one on financial crises, a second on financial innovation, and, on the policy side, a third on the monetary policy of the European Central Bank"-- Provided by publisher.